Uncovering the research evolution and hotspots of metabolism in renal cell carcinoma over the last decade - Liu, Yifan; He, Junzhe; Lyu, Donghao; Yang, Xinyue; Zhang, Haoyu; Tu, Siqi; Yao, Yuntao; Wei, Maodong; Li, Yuanan; Zhao, Zihui; Huang, Runzhi; Lu, Bingnan; et al. (Frontiers in Oncology, 2025)
BackgroundThe vital role metabolism plays in RCC, a global disease with huge disease burden, has been widely acknowledged. However, bibliometric analysis remains underexplored in the context of metabolism in RCC.MethodsThe Web of Science database was adopted to obtain relevant publications for further bibliometric analysis of countries, institutions, authors, journals, publications, references and keywords. Literature reading and keyword co-occurrence analysis were employed to figure out major points and hotspots in this field. The analysis was conducted by biblioshiny based on Bibliometrix package in R version 4.3.2.ResultsFrom 15 May 2015 to 15 May 2025, 3010 relevant publications were retrieved. China was the most productive country and USA was the country with the highest total citations. The most productive institution was “Harvard University”. WANG Y published 46 publications with an H-index of 16. Core journals were identified with Bradford’s law. Additionally, three major points and hotspots were identified and discussed through bibliometric analysis and targeted literature reading.ConclusionOur research provided a reference for future basic and clinical research through summarizing past research findings, analyzing current research hotspots, and prospecting the future development of research. “Metabolic alterations in RCC”, “Metabolic syndrome and RCC”, “Microbiome and RCC” were major points and hot spots in this field. In the future, a broader metabolic map could be made and more researches concerning metabolism during RCC treatment and drug resistance might bring more clinical significance.